Simultaneous trait selection strategies applied to genome-wide selection for the identification of superior genotypes - Silva, Lidiane Aparecida; Peixoto, Marco Antônio; Peixoto, Leonardo de Azevedo; Romero, Juan Vicente; Bhering, Leonardo Lopes (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the efficiency of direct and indirect selection in genome-wide selection (GWS) and to compare multivariate strategies applied to GWS via selection indices. Ten F2 populations with 800 individuals were simulated, considering four traits with different heritabilities. The simulated data were subjected to genomic selection analyses. The five following strategies of selection indices were developed and applied to GWS: weighting of marker effects by residual variance; coding and standardization of marker effects; application of the average to the marker effects; application of the Mulamba & Mock index to genomic genetic values; and coding and standardization of phenotypic values before the GWS analyses. The GWS methods were more efficient than phenotypic selection. The multivariate strategies provide a higher selection efficiency than the direct and indirect phenotypic selections and than the direct and indirect selections based on genomic genetic values and on the phenotypic selection index.